Bioavailable Strontium, Human Paleogeography, and Migrations in the Southern Andes: A Machine Learning and GIS Approach - Barberena, Ramiro; Cardillo, Marcelo; Lucero, Gustavo; le Roux, Petrus J.; Tessone, Augusto; Llano, Carina; Gasco, Alejandra; Marsh, Erik J.; Nuevo-Delaunay, Amalia; Novellino, Paula; Frigolé, Cecilia; Winocur, Diego; et al. (Frontiers in Ecology and Evolution, 2021)
The Andes are a unique geological and biogeographic feature of South America. From the perspective of human geography, this mountain range provides ready access to highly diverse altitudinally arranged ecosystems. The combination of a geologically and ecologically diverse landscape provides an exceptional context to explore the potential of strontium isotopes to track the movements of people and the conveyance of material culture. Here we develop an isotopic landscape of bioavailable strontium (87Sr/86Sr) that is applied to reconstruct human paleogeography across time in the southern Andes of Argentina and Chile (31º-34ºS). These results come from a macro-regional sampling of rodents (N= 65) and plants (N= 26) from modern and archaeological contexts. This ‘Southern Andean Strontium Transect’ extends over 350 km across the Andes, encompassing the main geological provinces between the Pacific coast (Chile) and the eastern lowlands (Argentina). We follow a recently developed approach to isoscape construction based on Random Forest regression and GIS analysis. Our results suggest that bioavailable strontium is tightly linked with bedrock geology and offers a highly resolved proxy to track human paleogeography involving the levels of territories or daily mobility and anomalous events that disrupt home ranges, such as migration. The southern Andes provide an ideal geological setting to develop this approach, since the geological variation in rock age and composition produces distinctive isotopic signatures for each main biogeographical region. Finally, we apply this framework to a set of results from human remains from the Uspallata Valley in Mendoza (Argentina), to assess the incidence of migration in the key period of the consolidation of agropastoral economies between AD 800-1400. The application of the isoscape to the values from human remains confirms the persistence of human groups with relatively restricted territories encompassing Uspallata and the adjacent Precordillera between AD 800-1500. We also identify a pulse of human migration between AD 1280-1420, shortly preceding the Inka conquest. Looking forward, we expect to converge with ongoing efforts in South America to build a continental research framework to track the movement of people, animals, and artefacts across space and time.